Development of a novel antibacterial peptide pam-5 via combination of phage display selection and computer-assisted modification - Yuen, Hawk Leong (2023)
The rapid acquisition and dissemination of antibiotic-resistance among pathogenic bacteria has been regarded as the major obstacle to effective treatment of bacterial infections. Therefore, development of alternative antibacterial agents is indeed an urgent need. Accumulating evidence have strongly proposed that antibacterial peptides (ABPs) are potential alternative antibacterial agents due to their unique features. However, isolation of these compounds from natural resources can be tedious and the yield is not ensuing. Moreover, certain natural ABPs were found toxic to mammalian cells, thus restricting their clinical use. Therefore, the objective of this study was to develop a potent ABP with minimal toxicity via phage-display selection followed by computer-assisted modification. Briefly, a 12-mer phage-displayed peptide library was used to identify peptides that bound to the cell surface of Pseudomonas aeruginosa (P. aeruginosa) with high affinity. The affinity selected peptide with the highest selection frequency was modified to PAM-5 (KWKWRPLKRKLVLRM) with enhanced antibacterial features by using online peptide database. Using in vitro microbroth dilution assay, PAM-5 was shown active against a panel of Gram-negative bacteria and selected Gram- iii positive bacteria. Interestingly, the peptide also exhibited similar bactericidal effect in ex vivo assay which was set up in human plasma. Scanning electron microscopy and SYTOX Green uptake assay revealed that PAM-5 was able to cause outer membrane disruption and inner membrane permeabilization to the bacteria, respectively. Additionally, the peptide was also able to bind to bacterial DNA as demonstrated by gel retardation assay. In time-kill assay, PAM-5 was shown able to cause complete bacterial elimination in 10 minutes. More importantly, PAM-5 was non-cytotoxic to Vero and HeLa cells and non-haemolytic to human erythrocytes at all concentrations tested for the antibacterial assays. Thus, this study showed that the combination of phage display screening and computer-assisted modification could be used to develop potent novel ABPs, and PAM-5 derived from these approaches is worth to be further elucidated for its potential clinical use.